2023
DOI: 10.3390/ijms24043881
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy and Ventricular Tachyarrhythmia: The Role of Biomarkers

Abstract: Left ventricular hypertrophy (LVH) refers to a complex rebuilding of the left ventricle that can gradually lead to serious complications—heart failure and life-threatening ventricular arrhythmias. LVH is defined as an increase in the size of the left ventricle (i.e., anatomically), therefore the basic diagnosis detecting the increase in the LV size is the domain of imaging methods such as echocardiography and cardiac magnetic resonance. However, to evaluate the functional status indicating the gradual deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 121 publications
1
0
0
Order By: Relevance
“…Hypertrophy of the heart muscle in hypertension individuals is defined not only by a rise in myocardial mass, but also by fibrous tissue growth and a reduction in intercellular coupling. These changes can result in the development of different arrhythmias [20,21]. The present study revealed a significant prevalence of LVH among patients diagnosed with AF, with a rate of 56%.…”
Section: Resultssupporting
confidence: 51%
“…Hypertrophy of the heart muscle in hypertension individuals is defined not only by a rise in myocardial mass, but also by fibrous tissue growth and a reduction in intercellular coupling. These changes can result in the development of different arrhythmias [20,21]. The present study revealed a significant prevalence of LVH among patients diagnosed with AF, with a rate of 56%.…”
Section: Resultssupporting
confidence: 51%